Assessing the influence of modifiable patient-related factors on complication rates after adult spinal deformity surgery. (1st November 2022) - Williamson, Tyler K.; Passfall, Lara; Ihejirika-Lomedico, Rivka; Espinosa, Annie; Owusu-Sarpong, Stephane; Lanre-Amos, Tomi; Schoenfeld, Andrew J.; Passias, Peter G.
Abstract : Aims: Postoperative complication rates remain relatively high after adult spinal deformity (ASD) surgery. The extent to which modifiable patient-related factors influence complication rates in patients with ASD has not been effectively evaluated. The aim of this retrospective cohort study was to evaluate the association between modifiable patient-related factors and complications after corrective surgery for ASD. Methods: ASD patients with two-year data were included. Complications were categorized as follows: any complication, major, medical, surgical, major mechanical, major radiological, and reoperation. Modifiable risk factors included smoking, obesity, osteoporosis, alcohol use, depression, psychiatric diagnosis, and hypertension. Patients were stratified by the degree of baseline deformity (low degree of deformity (LowDef)/high degree of deformity (HighDef): below or above 20°) and age (Older/Younger: above or below 65 years). Complication rates were compared for modifiable risk factors in each age/deformity group, using multivariable logistic regression analysis to adjust for confounders. Results: A total of 480 ASD patients met the inclusion criteria. By two years, complication rates were 72% ≥ one complication, 28% major, 21% medical, 27% surgical, 11% major radiological, 8% major mechanical, and 22% required reoperation. Younger LowDef patients with osteoporosis were more likely to suffer either a major mechanical (odds ratio (OR) 5.9 (95% confidence interval (CI) 1.1 to 36.9); p = 0.048) or radiological complication (OR 7.0 (95% CI 1.9 to 25.9); p = 0.003). Younger HighDef patients were much more likely to develop complications if obese, especially major mechanical complications (OR 2.8 (95% CI 1.1 to 8.6); p = 0.044). Older HighDef patients developed more complications when diagnosed with depression, including major radiological complications (OR 3.5 (95% CI 1.1 to 10.6); p = 0.033). Overall, a diagnosis of depression proved to be a risk factor for the development of major radiological complications (OR 2.4 (95% CI 1.3 to 4.5); p = 0.005). Conclusion: Certain modifiable patient-related factors, especially osteoporosis, obesity, and mental health status, are associated with an increased risk of complications after surgery for spinal deformity. Surgeons should look for these conditions when assessing a patient for surgery, and optimize them to the fullest extent possible before proceeding to surgical correction so as to minimize the prospect of postoperative morbidity. Cite this article: Bone Joint J 2022;104-B(11):1249–1255.